The effect of prenatal maternal stress on the hypothalamuspituitary- adrenal axis of the child at the age of 6 months - Nylund, Marjo (fi=Turun yliopisto|en=University of Turku|, 2018)
Introduction: Prenatal environment has been associated with fetal development. Stress during pregnancy might lead to child’s increased risk for adverse outcomes such as cardiovascular diseases, behavioural problems and mental health problems later in life. The mechanisms mediating these adverse outcomes are not fully understood but it is thought that the underlying mechanism could be the alterations that prenatal maternal stress causes to the stress regulatory systems. Hypothalamus-pituitary-adrenal (HPA) axis is the main stress regulation system in humans, which regulates the production and release of glucocorticoids, in human cortisol, from the adrenal cortex into circulation. Glucocorticoids are important in the fetal development. Prenatal stress might expose the children for excess amount of endogenous glucocorticoids and thus the stress might affect the development and function of the HPA-axis. It is also possible that prenatal exposure to maternal medications such as synthetic corticosteroids or selective serotonin reuptake inhibitors (SSRIs) may affect the child HPA-axis development. The aim of the study was to evaluate the effect of prenatal stress and maternal medication to the function of the HPA-axis of the child at the age of 6 months. Methods: In total 185 children withdrawn from the FinnBrain Birth Cohort Study at the age of 6 months entered the case-control study. 79 of the subjects had been exposed to prenatal stress. Maternal prenatal stress was evaluated at the gestational weeks 14, 24 and 34, and 3 and 6 months postpartum with standardized questionnaires for depressive, overall anxiety, and pregnancy-related anxiety symptoms (EPDS, SCL-90 and PRAQ-R2). HPA-axis function was evaluated measuring basal cortisol concentration from saliva sample collected at the study visit. Information about the long-term medications of the mother was obtained with questionnaires at the gestational weeks 14 and 34 and 6 months postpartum. Results: Prenatal stress was associated with elevated basal cortisol only in girls. Increased baseline cortisol of the girls was also linked with overall anxiety during the early pregnancy. In addition, prenatal depression during the mid-gestation was related to higher cortisol baseline in the prenatal stress exposed children. Overall anxiety at 6 months postpartum was associated with increased basal cortisol in prenatal stress exposed children but decreased basal cortisol in boys. Exposure to maternal thyroxine medication during the early pregnancy was linked with elevated basal cortisols and postnatal exposure to hormonal contraceptives via breastfeeding resulted in lower basal cortisol in girls only. Conclusions: Prenatal stress and maternal medication affected especially the HPA-axis of the girls. The results refer that the HPA-axis of the girls may be more susceptible to prenatal medication and stress effects.